The relationship between the humic degree of oil shale kerogens and their structural characteristics. (1st December 2017) - Wang, Qian; Hou, Yucui; Wu, Weize; Niu, Muge; Ren, Shuhang; Liu, Zhenyu
Highlights: The relationship between structural characteristics and kerogens' humic degree was studied. The aliphaticity and average methylene chain length decrease with increasing humic degree. The aromaticity and average aromatic cluster size increase with increasing humic degree. The existence forms of heteroatom species (O, N and S) in kerogens were determined. The heteroatom species change regularly with increasing humic degree of kerogens. Abstract: Elemental analysis, CP/MAS 13 C NMR, FTIR, XRD, XPS and ion-exchange experiment were used to study the structural characteristics of Longkou, Huadian and Yilan kerogens in an increasing order of humic degree. The relationship between their humic degree and structural characteristics was studied from three aspects: aliphatic structure, aromatic structure and heteroatom species (O, N and S). The results show that the kerogens are mainly composed of aliphatic structure, dominantly as CH2 chain. Moreover, the ratio of aliphatic carbon ( f al, aliphaticity) and average methylene chain length ( C n ) decrease with the increase of humic degree. In these kerogens, most of their aromatic clusters are separated by various bridge bonds or many CH2 long chains. Furthermore, the ratio of aromatic carbon ( f a, aromaticity) and average aromatic cluster size increase while the substitutive degree of aromatic ring decreases with increasing humic degree. With an increase in humic degree, the content of OCO (carboxyl and ester) decreases and the contents of CO (alcohol, phenol, and ether) increase. Moreover, the content of phenolic hydroxyl groups increases and the content of carboxyl groups decreases with increasing humic degree. The organic nitrogen in the kerogens is distributed as pyridinic nitrogen, amine nitrogen, pyrrolic nitrogen and chemisorbed nitrogen oxides. The contents of pyridinic nitrogen and chemisorbed nitrogen oxides increase while the contents of amino nitrogen and pyrrolic nitrogen decrease with increasing humic degree. In addition, organic sulfur in these kerogens exists as aromatic and aliphatic sulfur, sulfone and sulfoxide. The contents of aromatic sulfur and sulfoxide increase while the contents of aliphatic sulfur and sulfone decrease with increasing humic degree.